PENINGKATAN HASIL BELAJAR PADA MATERI “PERUBAHAN WUJUD BENDA” MELALUI PENERAPAN METODE DEMONSTRASI - Asnat Kabes,; Said Hindom,; walisda, walisda (Jurnal Cakrawala Ilmiah, 2025)
This study aims to determine the improvement of learning outcomes in the material of changes in the state of objects through the application of simple media-assisted demonstration methods for grade III students of Wartutin State Elementary School. This type of research is classroom action research which is carried out in two cycles, each cycle consisting of four components, namely planning, action, observation and reflection. Data collection techniques and tools used in this study are interviews, observations, documentation and tests. The results of the study showed that the application of simple media-assisted demonstration methods can improve student learning outcomes. The increase in the average class value from cycle I to cycle II increased by 7, namely from 59 to 72. Student learning outcomes achieved the success indicator of the Minimum Completion Criteria (KKM) of 100% percent. Based on the results of observations/observations carried out during the learning process, it shows that student activity which includes interaction between students, paying attention activities, working together in groups, expressing opinions, self-confidence, and courage to present groups in front of the class has increased.